Identifying the effect of refrigerant liquid level in receiver on energy efficiency and cooling performance of domestic freezers - Sukusno, Paulus; Nainggolan, Benhur; Jannus, Parulian; Nidhar, Ainun; Nufus, Tatun Hayatun; Rahman, Haolia (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates a domestic vapor-compression freezer system utilizing R404A refrigerant and a 0.75 kW-rated compressor, with a focus on the impact of different liquid refrigerant levels in the receiver on system performance and energy consumption. One major issue in household freezers is excessive energy use, particularly in systems lacking fluid regulation mechanisms such as a receiver. To explore this, an experimental setup was developed to test six operating conditions: one without a receiver and five with varying refrigerant fill levels in the receiver, ranging from less than 0% to over 60%. Experimental results showed that the freezer without a receiver recorded the highest Coefficient of Performance (COP) of 2.55 but also had the highest energy usage at 1.90 kWh. In contrast, the configuration with 30% refrigerant fill in the receiver demonstrated optimal performance, achieving a 47% reduction in compressor power, the lowest energy consumption (1.01 kWh), and an evaporator temperature reaching –31°C. These improvements are attributed to more stable refrigerant flow, enhanced subcooling, and better pressure regulation enabled by the receiver. The use of a liquid receiver allowed for smoother thermodynamic operation, minimizing energy loss through irregular phase distribution. The findings suggest that fine-tuning the refrigerant charge within the receiver can significantly improve the system’s energy efficiency, without the need for extensive redesign of main components. This approach offers a simple, low-cost, and effective solution, especially relevant for household and small-scale commercial freezer applications where practicality and long-term savings are priorities